Exploring psilocybin-assisted psychotherapy in the treatment of methamphetamine use disorder - Brett, Jonathan; Knock, Elizabeth; Korthuis, P. Todd; Liknaitzky, Paul; Murnane, Kevin S.; Nicholas, Christopher R.; Patterson, James C.; Stauffer, Christopher S. (Frontiers in Psychiatry, 2023)
Methamphetamine use disorder is a chronic relapsing condition, associated with substantial mental, physical, and social harms and increasing rates of mortality. Contingency management and psychotherapy interventions are the mainstays of treatment but are modestly effective with high relapse rates, while pharmacological treatments have shown little to no efficacy. Psilocybin-assisted psychotherapy is emerging as a promising treatment for a range of difficult-to-treat conditions, including substance use disorders; however, no studies have yet been published looking at psilocybin-assisted psychotherapy in the treatment of methamphetamine use disorder. Here we review the rationale for psilocybin-assisted psychotherapy as a potential treatment for this indication, and describe practical considerations based on our early experience designing and implementing four separate clinical trials of psilocybin-assisted psychotherapy for methamphetamine use disorder.